APLIKASI SEDIMEN DANAU TONDANO SEBAGAI MEDIA TANAM BAGI PERTUMBUHAN TANAMAN PAKCOY - Sinolungan, M. T.M.; Kumolontang, W. N.J. (Universitas Sam Ratulangi, 2017)
ABSTRACT Tondano Lake,Â one of vital naturalÂ resources at Minahasa Regency, North Sulawesi, has some functions and some problems, i.e.: sedimentation and lake shallowing. This research was conducted by using water hyacinth (Eichornia crassipes (Malt)) as compost/organic fertilizer and sediment of Tondano Lake as plant media for Packoy growth. This research has aimed to: 1) Test the composition of Tondano Lake sediment, 2) Test the composition of water hyacinth compost, and 3) Measure the growth of Pakcoy toward the given compost as a preliminary research (Pot Experiment). This was conducted: a) sediment sampling at the west part of Tondano Lake, b) sediment and compost analyses at Chemical and Soil Fertility Laboratory of Agriculture Faculty of Unsrat, c) planting Pakcoy in small pots with Group-Randomized Design for nine months in 2016. Results showed that, 1) sediment composition of Tondano Lake as the plant media has tested, 2) compost composition of water hyacinth has tested, and 3) Pakcoy growth toward the given compost as a preliminary research (Pot Experiment) has measured by height of plant, number of leaves, and freshedweight of crops, andso would applicable in further research due to the result of analyses was significantly different. Keywords: sediment, Tondano Lake, compost, water hyacinth, pakcoy